Antioomycete Nanoformulation for Biocontrol of English Walnut Crown and Root Rot Caused by Phytophthora cinnamomi - Aldo Salinas; Iván Montenegro; Yusser Olguín; Natalia Riquelme; Diyanira Castillo-Novales; Alejandra Larach; Laureano Alvarado; Guillermo Bravo; Alejandro Madrid; Juan E. Álvaro; Ximena Besoain (Plants)
In Chile and worldwide, walnut (Juglans regia L.) production faces significant losses due to crown and root rot caused by the phytopathogen Phytophthora cinnamomi. Currently, control methods have proven insufficient or unfavorable for the environment, increasing the need for sustainable alternatives. This research evaluates nanoemulsions based on extracts of medicinal plants endemic to Chile to control P. cinnamomi in walnut crops. The methodology included an in vitro test to determine the effective inhibitory concentrations of three nanoemulsions (N80, N90, and N100) on the mycelial growth of the phytopathogen, a test on walnut plants under controlled conditions, and two field tests using concentrations between 300 and 500 ppm. The in vitro results showed that the nanoemulsions could inhibit 90% of mycelial growth at 80 to 100 ppm concentrations. In the field, the N90 nanoemulsion at 500 ppm significantly reduced disease symptoms preventively and post-inoculation, compared with the control. This research is the first to study the use of nanoemulsions from native Chilean plants to control P. cinnamomi, showing potential to reduce the use of synthetic fungicides, contributing to safer and more ecological phytosanitary management.